Establecimiento de la metodología para aseguramiento de la calidad en ArcSight QA Costa Rica. - Aguilar-Mora, Alejandro Alberto (Instituto Tecnológico de Costa Rica, 2018)
The more successful qualities from the best companies are, those that can determinate which areas has a change of improvement and also the ones that are already changed and improved their process. Not just for searching strategic value, also for get better quality on the daily work for reducing the production cost to the maximum possible. The Microfocus company is the current owner of the intellectual property of ArcSight, which got in their product portfolio products for the cybersecurity and analysis of their network activity in order to prevent any attack or odd behaviors inside of the network. And this allows the customer of this products to detect and improve security on their information systems and infrastructure. And in order to ensure that his products will enable their clients to do so, they need be constantly delivered new versions of the products that requires to have a high level of quality for being effective. For this ArcSight has some QA teams that work constantly in order to ensure the quality of the products. Due to the independence of each QA team regarding their production activities and the products that work specifically, they don’t have a common methodology that allows to do the Quality Assurance process and also to be measured in order to improved it during the passing of time to avoid decadency of it. In this work is going to be explained a field research related to ArcSight Costa Rica division, that shows the analysis of the current quality assurance methodology in each QA team for the products on the portfolio. As a result of this research we have a proposal of a new methodology, focus on the quality assurance following the best industry practices regarding quality assurance for software and also the best practices for agile methodologies. Besides of bringing a standard for the day to day process, also brings the opportunity to it for growing and adapting during the passing of time and this enables to adapt to the organization necessities and avoid obsolescence of it. And in order to make it successful it gives a detailed implementation, following and maintain process but these steps are outside of the scope of the project.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2018.
Keywords: Estandarización; Prácticas; Procesos; Actores; Herramientas